2003
DOI: 10.1002/bsl.525
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of mental illness to targeted contact behavior toward state government agencies and officials

Abstract: Research in the burgeoning field of threat assessment has illuminated the importance of mental illness factors when considering risk of targeted violence-particularly related to government agencies and officials. The authors analyzed 127 cases investigated by a state law enforcement agency regarding threatening or other contacts toward public officials or state agency employees prompting security intervention. Univariate and discriminant analysis indicated that mentally ill subjects were significantly more lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 21 publications
2
32
0
Order By: Relevance
“…There is a modest literature that empirically examines threats (Calhoun, 1998;Dietz et al, 1991aDietz et al, , 1991bMeloy, 2001;Scalora, Baumgartner, & Plank, 2003). One of the few systematic studies of psychiatric assessment after uttering a homicidal threat reported nearly half to be psychotic and most of the rest personality disordered (MacDonald, 1968).…”
Section: The Assessment Processmentioning
confidence: 98%
“…There is a modest literature that empirically examines threats (Calhoun, 1998;Dietz et al, 1991aDietz et al, , 1991bMeloy, 2001;Scalora, Baumgartner, & Plank, 2003). One of the few systematic studies of psychiatric assessment after uttering a homicidal threat reported nearly half to be psychotic and most of the rest personality disordered (MacDonald, 1968).…”
Section: The Assessment Processmentioning
confidence: 98%
“…Factor analysis was conducted on the OTUSRS for community residents who sought help from CMHC during 2003(Zartaloudi, 2008, resulting in three factors. Factor 1, Interpersonal communication (items indicating the usefulness of seeking help and a positive history with social or informal help-seeking); Factor 2, Distrust (items indicating that others cannot be trusted); Factor 3, Isolation (items indicating the non-usefulness of seeking help and a negative history with social or informal helpseeking).…”
Section: Orientation Toward Utilization Of Social Resources Scale (Otmentioning
confidence: 99%
“…Factor analysis was conducted on the ATSPPHS for the population of the community residents who sought help from CMHC during 2003(Zartaloudi, 2008, resulting in four factors. Factor 1, Assertiveness toward help-seeking; Factor 2, Isolation; Factor 3, Ambivalence toward help-seeking; and Factor 4, Stigma.…”
Section: Attitudes Toward Seeking Professional Psychological Help Scamentioning
confidence: 99%
See 1 more Smart Citation
“…In an increasingly active research field, further detailed work on associations of concerning communications and approaches to public figures has been carried out in the USA (Scalora et al, ,b; Scalora, Baumgartner, & Plank, ; Schoeneman‐Morris, Scalora, Chang, Zimmerman, & Garner, ; Schoeneman et al, ) and in the UK (James et al, ; ,c; , et al, ,b), among other places. (A summary of contemporary research can be found in Hoffman, Meloy, & Sheridan, .)…”
mentioning
confidence: 99%